A novel composed index to evaluate the right ventricle free-wall adaptation against ventricular wall stress in acute pulmonary embolism - Hakgör, Aykun; Tokgöz Demircan, Hacer Ceren; Keskin, Berhan; Tanyeri, Seda; Kültürsay, Barkın; Tosun, Ayhan; Akbal, Özgür Yaşar; Külahçıoğlu, Şeyhmus; Karagöz, Ali; Türkday Derebey, Sevim; Bayram, Zübeyde; Efe, Süleyman; et al. (NLM (Medline), 2023)
Background: Pulmonary embolism severity index and simplified pulmonary embolism severity index have been utilized in initial risk evaluation in patients with acute pulmonary embolism. However, these models do not include any imaging measure of right ventricle function. In this study, we proposed a novel index and aimed to evaluate the clinical impact. Methods: Our study population comprised retrospectively evaluated 502 patients with acute pulmonary embolism managed with different treatment modalities. Echocardiographic and computed tomographic pulmonary angiography evaluations were performed at admission to the emergency room within maximally 30 minutes. The formula of our index was as follows: (right ventricle diameter × systolic pulmonary arterial pressure-echo)/(right ventricle free-wall diameter × tricuspid annular plane systolic excursion). Results: This index value showed significant correlations to clinical and hemodynamic severity measures. Only pulmonary embolism severity index, but not our index value, independently predicted in-hospital mortality. However, an index value higher than 17.8 predicted the long-term mortality with a sensitivity of 70% and specificity of 40% (areas under the curve = 0.652, 95% CI, 0.557-0.747, P = .001). According to the adjusted variable plot, the risk of long-term mortality increased until an index level of 30 but remained unchanged thereafter. The cumulative hazard curve also showed a higher mortality with high-index value versus low-index value. Conclusions: Our index composed from measures of computed tomographic pulmonary angiography and transthoracic echocardiography may provide important insights regarding the adaptation status of right ventricle against pressure/wall stress in acute pulmonary embolism, and a higher value seems to be associated with severity of the clinical and hemodynamic status and long-term mortality but not with in-hospital mortality. However, the pulmonary embolism severity index remained as the only independent predictor for in-hospital mortality.
Keywords: Acute Pulmonary Embolism; Computed Tomography; Pulmonary Embolism Severity Index; Risk Prediction; Right Ventricle; Transthoracic Echocardiography